EFEKTIVITAS KERJA KANTOR REGIONAL XII BADAN KEPEGAWAIAN NEGARA PEKANBARU - Ayu Permata Sari; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine: 1) the effectiveness of the work of Regional Office XII of the Pekanbaru State Civil Service. 2) factors that hinder the effectiveness of the work of Regional Office XII of the Pekanbaru State Personnel Agency. This study uses the theory of effectiveness, Mahmudi (2015) explains that effectiveness is the relationship between output and the purpose of the large contribution (donation) of output to achieving goals, the more effective the organization with input, process, output and outcome indicators. The research method in this study is a qualitative method with data collection through interviews, observation and documentation. Informants in this study were the selection committee from Kanreg XII BKN, proposing agencies and CPNS applicants. The results of the study show that the effectiveness of the Regional Office XII of the Pekanbaru State Personnel Agency has been effective, this is proven by the fulfillment of several indicators in accordance with the effectiveness assessment indicators. This is proven by competent human resources, supporting facilities such as adequate facilities and infrastructure. Although, there were still participants who complained that there were deficiencies and that they were not fully optimal because there were several things that needed attention to be improved. The inhibiting factors in this research are inconsistent provisions or rules set by the committee, as well as the limitations of internet network facilities and backup electricity.Keywords: Effectiveness, Computer Assisted Test (CAT), Procurement, Candidates for Civil Servants (CPNS)